2014
DOI: 10.1038/ng.2985
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genetic study in East Asians identifies six new loci associated with colorectal cancer risk

Abstract: Known genetic loci explain only a small proportion of the familial relative risk of colorectal cancer (CRC). We conducted the largest genome-wide association study in East Asians with 14,963 CRC cases and 31,945 controls and identified six new loci associated with CRC risk (P = 3.42 × 10−8 to 9.22 × 10−21) at 10q22.3, 10q25.2, 11q12.2, 12p13.31, 17p13.3 and 19q13.2. Two of these loci map to genes (TCF7L2 and TGFB1) with established roles in colorectal tumorigenesis. Four other loci are located in or near genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
221
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 214 publications
(229 citation statements)
references
References 83 publications
8
221
0
Order By: Relevance
“…The Stage I study was a meta-analysis of results of AM and ANM association using data generated from the Shanghai Genome-Wide Association Studies (SGWAS), which included female participants of the Shanghai Breast Cancer Genetics Study (SBCS) (Zheng et al 2009), the Shanghai Endometrial Cancer Study (SECS) (Long et al 2012), the Shanghai Type II Diabetes Studies (ST2DS) , the Shanghai Colorectal Cancer Study (SCRCS) (Jia et al 2013;Zhang et al 2014), and other ancillary studies using the Shanghai Women's Health Study (SWHS) samples (Petersen et al 2010;Abnet et al 2010). All these studies, except for the SBCS and SECS, drew women from the SWHS, a population-based cohort study (Zheng et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The Stage I study was a meta-analysis of results of AM and ANM association using data generated from the Shanghai Genome-Wide Association Studies (SGWAS), which included female participants of the Shanghai Breast Cancer Genetics Study (SBCS) (Zheng et al 2009), the Shanghai Endometrial Cancer Study (SECS) (Long et al 2012), the Shanghai Type II Diabetes Studies (ST2DS) , the Shanghai Colorectal Cancer Study (SCRCS) (Jia et al 2013;Zhang et al 2014), and other ancillary studies using the Shanghai Women's Health Study (SWHS) samples (Petersen et al 2010;Abnet et al 2010). All these studies, except for the SBCS and SECS, drew women from the SWHS, a population-based cohort study (Zheng et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, it is more important to know whether the SNPs can be used to stratify people in the population in terms of their risk of developing cancer. While each SNP risk allele is associated with only a small increase in risk (e.g., 5-25%) [5][6][7], carriers of many…”
Section: Background and Aimmentioning
confidence: 99%
“…compared with -69A and 4150T alleles in two independent case-control sets (18). A genome-wide association study performed by Zhang et al (26) indicated that rs4246215 (4150G>A), variant of the FEN1 gene, was associated with colorectal cancer in an East Asian population.…”
Section: Discussionmentioning
confidence: 99%